Where Is All the Deviance? Liminal Prescribing and the Social Networks Underlying the Prescription Drug Crisis. (March 2023) - Zhang, Victoria (Shu); Mohliver, Aharon Cohen; King, Marissa
The misuse of prescription drugs is a pressing public health crisis in the United States that is fueled by high-risk prescribing. We show that high-risk prescribing comprises two distinct practices: (1) routinely overprescribing to patients whose prescription - fill patterns are consistent with misuse or abuse, which conforms to the definition of deviance in sociology, and (2) routinely overprescribing to patients whose prescription-fill patterns are within possible bounds of medical use, which does not. We call the second practice "liminal prescribing, " a term that indicates it is legally and morally ambiguous. Using 213.9 million prescriptions to construct a four-year panel of the patient-sharing networks of 500, 472 physicians, we find that deviant and liminal prescribers have starkly different social network structures and social influence processes; larger and more cohesive networks among prescribers are associated with more deviance but less liminality. Physicians' ties to liminal prescribers increase liminal prescribing but do not increase deviance. Our results suggest that liminal prescribing is distinct from deviant prescribing and is not a milder form of deviant prescribing. Liminal prescribing is far more prevalent than deviance and accounts for most of the oversupplied benzodiazepines in our dataset (55.8 versus 8.7 percent, respectively). Our study highlights that the social structures supporting liminal practices differ from those that support either rule-abiding practices or deviance.